(untitled) (lectio difficilior, 2014)
This essay has its origins in a seminar about feminist theology at the University of Bern in the autumn term 2013. The seminar focused among other things on the many different perspectives feminist theories can have on biblical texts. Based on the rereading of the infancy story of Jesus depicted by the Roman Catholic theologian Jane Schaberg (1938-2012) in The Illegitimacy of Jesus (1990), the development of the motive of the virgin birth, which is connected to illegitimate conception and sexual violence, is examined in light of another two texts: On the one hand the novel Das Geschenk (2006) by Maria Elisabeth Straub, which is conceived as Mary’s monologue; on the other hand a Christmas sermon (2013) by Maja Zimmermann-Güpfert. It discusses the topic of sexual assault on women from which point the virgin birth can be interpreted anew.